How to plan TV campaigns - Williams, Steve (Henry Stewart Talks, 2009)
Introduction and market context, Exploring the 5 types of TV plans, Burst, Pulse, Drip and continuity, Specific environment, Direct response, Implications for planning in the third age
Archived at 2022/04/07